Assessment of quality of life of melasma patients as per melasma quality of life scale (MELASQoL) - Priyanka N Dodmani; Ashish R Deshmukh (Wolters Kluwer Medknow Publications, 2020)
Background: Melasma is the most common cause of facial melanoses in Indian population. It most commonly affects women of reproductive age group. Melasma poses a significant impact on social and psychological health. Aim: To study specific aspects of life affected in patients' life by melasma and study the effect of melasma on their level of functioning using melasma quality of life scale (MELASQoL). Materials and Methods: In a cross-sectional descriptive study of 160 patients of melasma with any severity (assessed by MASI) were included. QoL of the patients was assessed using MELASQoL scale based on three domains of life e.g. emotional, social and recreation-leisure. Results: MELASQoL score was calculated for each patient. As per score, QoL in young, females and married patients were more affected than others. Patients having late onset of the disease and short duration are more affected. We found that half of patients were having moderate score, 46% of patients having mild score and only 4% of patients having severe score. In our study most affected domain of life was emotional well-being. Conclusion: Melasma causes a significant effect on QoL in many aspects of daily life. There is no significant correlation between MASI score and QoL affected. There is a need for patient counseling and development of educational programs and appropriate psychological intervention.